Lei de Cotas e Sisu: análise dos processos de escolha dos cursos superiores e do perfil dos estudantes da UFMG antes e após as mudanças na forma de acesso às Instituições Federais - Brescia Franca Nonato (2018)
The Sisu and the Law of Quotas changed significantly the form of access to public higher education in Brazil, creating the expectation of greater equality of opportunities among the candidates. During doctors degree course, we investigated how the Sisu, articulated with the Law of Quotas, influenced the process of choosing the higher courses, analyzing its implications for a possible democratization of the university. In other words, the effects of Sisu and the Law of Quotas were questioned on the process of choosing the higher courses and indirectly, on the social and scholastic profile of the new university students. Seeking to understand how these policies, especially the Law of Quotas, which has the intention of being democratizing, contribute or not to this process. In the research were analyzed data of the enrollment questionnaires of 2012 and 2016, applied to all the new entrants of the UFMG, and data of an independent questionnaire applied to 1271 students of four courses: Law course, Nursing, Medicine and Pedagogy. These courses were selected because they occupy very contrasting positions in terms of selectivity and expected material and symbolic return. The hypothesis, greatly strengthened by the data that will be presented, is that Sisu and Law of Quotas have different effects, depending on the position of the courses in the hierarchies that mark Higher Education. In the case of the UFMG, as will be discussed, the changes in the general profile of the university students were relatively small, in other words, there may have been a change in the profile of the candidate, but not of the entrant. The courses analyzed on the research have experienced very significant changes in the composition of their students and these have occurred in different or even opposite directions: this way we can presume of a relative elitism of the traditionally more accessible courses and a relative democratization of the most selective courses. The result of this movement was a reduction of the differences among the publics that studies one of the four courses, suggesting a relative reduction of the internal differences in the UFMG.